PEMBUATAN DAN UJI ORGANOLEPTIK SELAI LEMBAR DARI KOMBINASI TOMAT (Lycopersicum esculentum Mill) DAN KULIT BUAH NAGA MERAH (Hylocereus costaricensis cortex) SEBAGAI SUPLEMEN KAYA ANTIOKSIDAN - Septiani, Windy; Handayani, Reti Puji; Puspariki, Jenta (Sekolah Tinggi Ilmu Kesehatan Holistik, 2020)
Background: In the market, more and more food products are rich in antioxidant compounds, but red dragon fruit peel (Hylocereus costaricensis cortex) which is considered as waste contains high levels of antioxidants. Tomato fruit (Lycopersicum esculentum Mill) has very strong antioxidant activity because it contains lycopene which is the main pigment in tomatoes. Purpose: This study aims to make a combination sheet jam preparation of tomatoes and dragon fruit peel as an antioxidant-rich supplement that is easy to safe, practical and healthy for public consumption. Methods: The research method used is action research using research instruments in the form of an organoleptic test sheet and a preference test. Preparations made with the composition ratio of tomatoes and red dragon fruit skin, each formula is 100 grams of tomatoes :100 grams of red dragon fruit skin and a variety of sweeteners for F I as much as 40 grams, for F II as much as 50 grams and sweetener for F III as much as 60 grams. Results: The results of the organoleptic test at room temperature (15-30oC) showed that there was a change from day 6 to day 21, while the organoleptic test results at cold temperatures (± 4oC) had no change from day 1. Until the 21st day, the result of the favorite sheet jam test was formula 2, which was 86.6%. Conclusion: The conclusion that can be obtained is the result of the best composition variation is formula II with the number of tomatoes and dragon fruit skin is 1: 1 with added sugar as much as 50 grams. This is because the physical stability is good, namely organoleptic color, smell, taste, stable form does not have many fungi.